Microwave Photonics, 2007 Interntional Topical Meeting On 2007
DOI: 10.1109/mwp.2007.4378174
|View full text |Cite
|
Sign up to set email alerts
|

Bragg Gratings (BG) structures and slow-light approach for the processing of RF signals over large bandwidths

Abstract: Implementation of optical delay lines for microwave photonics requires the definition of dispersive structures able to perform large time delays over large RF bandwidths. Slow light approach and Chirped Bragg Gratings are proposed to overcome conventional limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[17] Kaba reported that multistage gratings, increasing grating length, or other techniques could enhance the effect of time delay. [18] Chen et al combined stimulated brillouin scattering (SBS) and FBG to increase the delay time. The delay time increased from 0.06-1.473 ns due to the SBS.…”
Section: Fbg Slow Lightmentioning
confidence: 99%
“…[17] Kaba reported that multistage gratings, increasing grating length, or other techniques could enhance the effect of time delay. [18] Chen et al combined stimulated brillouin scattering (SBS) and FBG to increase the delay time. The delay time increased from 0.06-1.473 ns due to the SBS.…”
Section: Fbg Slow Lightmentioning
confidence: 99%